Modified nano magnetic particles and magnetic particle grafted polymer fiber membrane fabric containing same

Through the application of modified nanomagnetic particles and magnetic particle graft polymer fiber membrane fabrics, the problem of nucleic acid loss in magnetic bead method is solved, and the yield of nucleic acid extraction and the accuracy of detection are improved.

CN119823395APending Publication Date: 2025-04-15BOE TECHNOLOGY GROUP CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202311321754.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-12
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

During the cleaning and purification steps of the magnetic bead method, there is a large amount of nucleic acid loss, resulting in a low yield of nucleic acid extraction, affecting the accuracy of nucleic acid detection.

Method used

A modified nanomagnetic particles were developed and a magnetic particle grafted polymer fiber membrane fabric was prepared by electrospinning technology to improve the recovery rate of nucleic acids and the accuracy of detection.

Benefits of technology

Through the application of modified nanomagnetic particles and magnetic particle graft polymer fiber membrane fabrics, the recovery rate of nucleic acid is significantly improved, reaching more than 95%, enhancing the accuracy and credibility of nucleic acid detection.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119823395A_ABST
    Figure CN119823395A_ABST
Patent Text Reader

Abstract

The invention provides a modified nano magnetic particle and a magnetic particle grafted polymer fiber membrane fabric containing the same. The modified nano magnetic particles are magnetic particles grafted with polymer fibers; wherein the polymer fibers are selected from one or more of polyvinyl acetal fibers, polyvinyl acetal derivative fibers, polyvinyl alcohol copolymer derivative fibers, polyvinylpyrrolidone fibers, polyvinylpyrrolidone derivative fibers, polyhydroxy polyester acetal fibers and polyhydroxy polyester acetal derivative fibers. The modified nano magnetic particles have the capacity of adsorbing nucleic acid, and the magnetic particle grafted polymer fiber membrane fabric prepared by taking the modified nano magnetic particles as a raw material and adopting an electrostatic spinning technology can be applied to full-automatic nucleic acid extraction, so that the nucleic acid recovery rate of nucleic acid extraction is obviously improved, and the accuracy and credibility of nucleic acid detection are favorably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of biomaterials, and specifically comprises a modified nano magnetic particle and a magnetic particle grafted polymer fiber membrane fabric comprising the modified nano magnetic particle. Background Art

[0002] Nucleic acid is one of the most basic substances for all kinds of life. It not only plays the role of storing and transmitting genetic information, but also plays a decisive role in a series of major life phenomena such as growth, inheritance, and mutation. As a molecular diagnostic technology, nucleic acid testing can obtain relevant information such as the progression of human diseases and potential risks through the detection and analysis of human nucleic acid. It is widely used in many fields such as oncology medicine, reproductive medicine, and pharmacy.

[0003] Nucleic acid extraction, as the primary link of nucleic acid detection, plays an extremely important role in clinical molecular diagnosis. Whether high-quality nucleic acid can be obtained is the key to giving correct diagnostic results later. The magnetic bead method is a nucleic acid extraction method that uses magnetic beads with non-specific adsorption of nucleic acid to adsorb nucleic acid from lysed cell solution, and separates the magnetic beads carrying nucleic acid from the solution containing impurities such as protein and cell fragments by magnetic adsorption. The magnetic beads carrying nucleic acid are then placed in different washing tanks for washing and purification to improve the purity of the adsorbed nucleic acid. Finally, the nucleic acid is separated from the magnetic beads by elution, thereby achieving high-quality nucleic acid extraction.

[0004] With the development of high-throughput sequencing technology (NGS technology), clinical requirements for high-throughput and automation of molecular diagnosis and nucleic acid detection are increasing. The use of automatic nucleic acid extraction devices for nucleic acid extraction has become the mainstream. The realization of automation has significantly improved the extraction efficiency. However, in actual applications, it is found that a large amount of nucleic acid will be lost during the cleaning and purification steps of the magnetic bead method, resulting in a low nucleic acid extraction yield, which in turn affects the accuracy of the final nucleic acid detection. Therefore, it is urgent to improve the cleaning and purification steps of the magnetic bead method to meet the needs of clinical diagnosis at this stage. Summary of the invention

[0005] In view of the above problems existing in the prior art, the first object of the present invention is to provide a modified nano-magnetic particle. 3 O 4 The nanomagnetic particles are surface-modified and a surfactant is added to form an emulsion, which promotes the uniform dispersion of the modified nanomagnetic particles in the solution and is beneficial for controlling the particle size of the modified nanomagnetic particles within a range suitable for nucleic acid extraction. At the same time, the surface of the modified nanomagnetic particles is hydrophobicized to further improve the hydrophobic effect of the modified nanomagnetic particles and increase the capture efficiency of nucleic acids. Therefore, the modified nanomagnetic particles can be widely used in the fields of cell sorting, immunoassay, nucleic acid analysis, biochip preparation, and microbial detection.

[0006] The second object of the present invention is to provide a method for preparing the modified nanomagnetic particles as described above.

[0007] The third object of the present invention is to provide an application of the modified nanomagnetic particles as described above in cell sorting, immunoassay, nucleic acid analysis, biochip preparation and microbial detection.

[0008] The fourth object of the present invention is to provide a free nucleic acid extraction kit.

[0009] The fifth object of the present invention is to provide a magnetic particle grafted polymer fiber membrane fabric. The magnetic particle grafted polymer fiber membrane fabric also has a strong ability to adsorb nucleic acids. When used in the magnetic bead method for nucleic acid extraction, it avoids the loss of nucleic acids caused by magnetic bead deposition in the washing and purification steps, which is beneficial to improve the recovery rate of nucleic acids and improve the accuracy and reliability of its test.

[0010] The sixth object of the present invention is to provide a method for preparing the magnetic particle grafted polymer fiber membrane fabric as described above.

[0011] The seventh object of the present invention is to provide an application of the magnetic particle grafted polymer fiber membrane fabric as described above in nucleic acid extraction.

[0012] To achieve the above first object, the technical solution adopted by the present invention includes:

[0013] The present invention discloses a modified nano-magnetic particle, wherein the modified nano-magnetic particle is a magnetic particle grafted with polymer fibers;

[0014] The polymer fiber is selected from one or more of polyvinyl acetal fiber, polyvinyl acetal derivative fiber, polyvinyl alcohol copolymer derivative fiber, polyvinyl pyrrolidone fiber, polyvinyl pyrrolidone derivative fiber, polyhydroxy polyester acetal fiber, and polyhydroxy polyester acetal derivative fiber.

[0015] With the development of high-throughput sequencing technology, technicians are more inclined to use simple-to-operate and automated automatic nucleic acid extractors for nucleic acid extraction. The principle of the automatic nucleic acid extractor is to use a cylindrical magnetic rod wrapped with a magnetic rod sleeve to first adsorb magnetic beads with nucleic acids and other impurities (such as proteins, inorganic salts, solvent residues, etc.) on the outer surface of the magnetic rod sleeve, and then extend the cylindrical magnetic rod into different washing tanks one by one to complete the removal of impurities and improve the quality of nucleic acids. The specific operation is: after extending into the washing tank, the cylindrical magnetic rod needs to be withdrawn from the magnetic rod sleeve, and the magnetic beads adsorbed on the outer surface of the magnetic rod sleeve lose their magnetic force and sink into the washing solution under the action of gravity, and then the magnetic rod sleeve is vibrated up and down to make the magnetic beads fully contact with the washing solution. The washing solution will remove specific impurities on the surface of the magnetic beads, and then the cylindrical magnetic rod is put back into the magnetic rod sleeve, and the cleaned magnetic beads are adsorbed on the magnetic rod sleeve again. After the adsorption is completed, the magnetic rod sleeve and the magnetic rod move synchronously, and then extend into another washing tank to repeat the previous operation, and finally most of the impurities can be removed to achieve the purpose of nucleic acid cleaning and purification. However, since most of the magnetic beads are deposited at the bottom of the washing solution, the effective area of ​​the cylindrical magnetic rod is limited, resulting in a reduced recovery rate of the magnetic beads. Each washing will cause a certain loss of magnetic beads. After several washing operations, the final number of magnetic beads will be affected, resulting in a low yield of nucleic acid extraction and large differences between different batches.

[0016] In order to solve this problem, the present invention firstly develops a modified nanomagnetic particle capable of adsorbing nucleic acid, and converts Fe 3 O 4 The nanoparticles were modified in three ways: the first was the modification of the modifier, the second was the modification of Fe with a silica layer. 3 O 4 Nano magnetic beads, the third is to graft polymer fibers outside the silicon coating, which is conducive to better control of the polymerization reaction and make the obtained nano magnetic particles more uniform in size. Then the nano magnetic particles are prepared into fiber membrane fabrics using electrostatic spinning technology. Through this design, more magnetic particles can be fixed on the fiber membrane fabric, and the fiber membrane fabric is better fixed on the magnetic rod sleeve, ultimately ensuring the recovery rate of magnetic beads every time cleaning and reducing the loss of magnetic beads.

[0017] Furthermore, the magnetic particles have a core-shell structure, including a magnetic material as a core and a silicon coating layer as an outer shell; the magnetic material is selected from modified Fe 3 O 4 Nanomagnetic beads. This is a classic core-shell structure in the art. Those skilled in the art can also modify the core-shell structure appropriately to meet the application requirements in the art. For example, the magnetic particles include polymer microspheres as the core, a magnetic coating layer as the interlayer, and a silicon coating layer as the shell. The polymer microspheres can be polystyrene microspheres, polyphenylene propylene microspheres, etc. The material used for the magnetic coating layer can be Fe 3 O4 , Fe 2 O 3 Etc. Similarly, those skilled in the art can also perform functional modification on the silicon encapsulation layer, introducing a functional group such as a carboxyl group or an amino group to replace the silanol group, which is not specifically limited here.

[0018] Further, the modified Fe 3 O 4 Nano-magnetic beads are Fe-based nanoparticles with surfaces modified by silane or oleic acid. 3 O 4 Nanomagnetic beads. It should be noted that the Fe 3 O 4 Nanomagnetic beads can be purchased directly from the market, or synthesized by the classical coprecipitation method. The present invention does not limit the source of the nanomagnetic beads. 3 O 4 Nanomagnetic beads can also be replaced by other commonly used magnetic substances that can adsorb nucleic acids, such as γ-Fe 2 O 3 Magnetic beads.

[0019] Furthermore, the groups contained in the polymer fiber are grafted onto the surface of the silicon coating layer through covalent bonds; the groups include but are not limited to one or more of amino, carboxyl, hydroxyl, amide, and ester groups.

[0020] Furthermore, the polymer fiber is selected from polyvinyl butyral fiber.

[0021] Furthermore, the average particle size of the modified nanomagnetic particles is 150-250 nm, preferably 200 nm.

[0022] To achieve the above second purpose, the technical solution adopted by the present invention includes:

[0023] The present invention discloses a method for preparing the modified nanomagnetic particles as described above, comprising the following steps:

[0024] Add water to the polymer, heat it to 80-95° C. after it is fully swollen, then add magnetic particles, adjust the pH to 4-6.5, add a blocking agent after stirring, and continue the reaction for 20-40 minutes to obtain the modified nano magnetic particles.

[0025] Furthermore, the sealing agent includes but is not limited to one or more aldehyde compounds such as formaldehyde, acetaldehyde, propionaldehyde, butyraldehyde and glutaraldehyde.

[0026] Furthermore, the polymer includes but is not limited to one or more of polyvinyl alcohol, polyvinyl pyrrolidone and polyhydroxy polyester, and has a molecular weight of 50,000-80,000, preferably polyvinyl alcohol.

[0027] Furthermore, the mass ratio of the magnetic particles, polymer and blocking agent is 1-2:10:2-4; illustratively, the mass ratio of the magnetic particles, polymer and blocking agent can be 1:10:2, 1:10:3, 1:10:4, 2:10:2, 2:10:3, 2:10:4 and the like.

[0028] Furthermore, the magnetic particles are prepared according to the following steps, which are only used as an example here. Those skilled in the art may use other preparation processes to synthesize magnetic particles with the same or similar functions. The preparation process includes:

[0029] It should be noted that the preparation method is carried out under an inert atmosphere throughout the process;

[0030] S1. Mix water-soluble iron salt and water evenly, add precipitant, and react at 60-80℃ for 4-6h to obtain Fe 3 O 4 Nano magnetic beads, then add the modifier, continue to react at the same temperature for 20-40 minutes, separate the solid and liquid, and obtain the modified Fe 3 O 4 Nanomagnetic beads;

[0031] S2, to modified Fe 3 O 4 Add silicon source, surfactant and deionized water to the nanomagnetic beads, mix them evenly to obtain a uniform emulsion, then add organic solvent and catalyst, and react at room temperature for 4-6 hours to obtain silicon-coated modified Fe 3 O 4 Nanomagnetic beads.

[0032] Furthermore, in order to ensure the availability of Fe 3 O 4 For the nanomagnetic beads, the water-soluble iron salt should be a combination of a water-soluble divalent iron salt and a water-soluble trivalent iron salt; illustratively, the water-soluble divalent iron salt includes but is not limited to one or more of ferrous chloride, ferrous nitrate, and ferrous sulfate; the water-soluble trivalent iron salt includes but is not limited to one or more of ferric chloride, ferric nitrate, and ferric sulfate;

[0033] The precipitant is not limited to one or more of sodium hydroxide, potassium hydroxide and ammonia water;

[0034] The modifier includes but is not limited to one or more of oleic acid, undecylenic acid, fatty alcohol polyoxyethylene ether and acetaminophen;

[0035] The silicon source includes, but is not limited to, one or more of ethyl orthosilicate, methyl orthosilicate, water glass and silicon tetrachloride.

[0036] The surfactant includes, but is not limited to, one or more of non-ionic surfactants such as Triton X-100, NP-40 and Tween.

[0037] The catalyst is selected from one or more of ammonia water, ethanolamine, sodium hydroxide, potassium hydroxide, hydrochloric acid and sulfuric acid.

[0038] To achieve the third objective, the technical solution adopted by the present invention includes:

[0039] The present invention discloses an application of the modified nanomagnetic particles in cell sorting, immune analysis, nucleic acid analysis, biochip preparation and microbial detection.

[0040] To achieve the fourth objective, the technical solution adopted by the present invention includes:

[0041] The invention discloses a free nucleic acid extraction kit comprising the modified nanomagnetic particles as described above.

[0042] Furthermore, the free nucleic acid extraction kit also includes a lysis binding solution, a cleaning agent and an eluent for decomposing the substance to be tested, and those skilled in the art can adjust them according to different application requirements.

[0043] To achieve the fifth objective, the technical solution adopted by the present invention includes:

[0044] The invention discloses a magnetic particle grafted polymer fiber membrane fabric. The magnetic particle grafted polymer fiber membrane fabric is prepared by using the modified nano magnetic particles as raw materials.

[0045] To achieve the sixth objective, the technical solution adopted by the present invention includes:

[0046] The present invention discloses a method for preparing the above-mentioned magnetic particle grafted polymer fiber membrane fabric, comprising the following steps:

[0047] The modified nano-magnetic particles are dissolved in an organic solvent, stirred evenly to obtain a spinning solution, and then electrostatic spinning is used to prepare the solution.

[0048] Furthermore, the concentration of the modified nanomagnetic particles in the spinning solution is 7-15wt%; illustratively, the concentration of the modified nanomagnetic particles in the spinning solution can be 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt% and the like.

[0049] Further, the conditions of the electrospinning are:

[0050] The voltage of electrospinning is 10-15 kV, the distance between the syringe needle and the receiving plate is 8-15 cm, the flow rate of the spinning solution is 1-1.5 mL / h, and the electrospinning time is 10-20 min.

[0051] To achieve the seventh objective, the technical solution adopted by the present invention includes:

[0052] The present invention discloses an application of the magnetic particle grafted polymer fiber membrane fabric in automatic nucleic acid extraction.

[0053] Furthermore, the application includes:

[0054] The magnetic particle grafted polymer fiber membrane fabric is wrapped on the outer surface of the magnetic rod sleeve, and then the nucleic acid is extracted, cleaned and purified.

[0055] Beneficial effects of the present invention:

[0056] The invention discloses a modified nano magnetic particle. The modified nano magnetic particle has the ability to adsorb nucleic acid and has uniform particle size, and has broad application prospects in automatic nucleic acid extraction.

[0057] The present invention also discloses a magnetic particle grafted polymer fiber membrane fabric prepared by electrostatic spinning technology using modified nano-magnetic particles as raw materials. The magnetic particle grafted polymer fiber membrane fabric is sleeved on the outer surface of a magnetic rod, which can significantly improve the nucleic acid recovery rate and concentration during nucleic acid extraction. The nucleic acid recovery rate reaches more than 95%, and the stability between different batches is good, which is conducive to improving the accuracy and reliability of nucleic acid detection, and has broad application prospects and commercial value. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] The specific implementation modes of the present invention will be further described in detail below in conjunction with the accompanying drawings.

[0059] Figure 1 A schematic diagram of the synthesis of modified nanomagnetic particles prepared in Example 1 is shown.

[0060] Figure 2 The silicon-coated modified Fe prepared in Example 1 is shown 3 O 4 TEM image of nanomagnetic beads.

[0061] Figure 3 The silicon-coated Fe prepared in Comparative Example 1 is shown 3 O 4 TEM image of nanomagnetic beads. DETAILED DESCRIPTION

[0062] In order to more clearly illustrate the present invention, the present invention is further described below in conjunction with preferred embodiments and drawings. It should be clear that the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0063] Example 1

[0064] 1)Fe 3 O 4 Synthesis of nanomagnetic beads:

[0065] In a 500mL three-necked flask, add 300mL of distilled water and pass N 2 Continue for 30 min, keep nitrogen atmosphere in the subsequent steps, add 5 g FeCl 3 6H 2 O, stir until all dissolved, then add 2g FeCl 2 ·4H 2 O, continue stirring until all dissolved, then heat to 80°C, add 20mL 25% ammonia solution, keep at 80°C for 4h to obtain Fe 3 O 4 Nanomagnetic beads.

[0066] 2) Modified Fe 3 O 4 Synthesis of nanomagnetic beads:

[0067] Maintaining 80°C, add 250 mg of oleic acid (300 μL) in 5 mL of acetone, then add 5 mL of 28% ammonia water, continue stirring at 80°C for 30 min, then slowly cool to room temperature, separate the magnetic beads with a magnet, wash the separated magnetic beads with ethanol, and dry them to obtain modified Fe 3 O 4 Nanomagnetic beads.

[0068] 3) Silicon-coated modified Fe 3 O 4 Synthesis of nanomagnetic beads:

[0069] To modify Fe 3 O 4 25 mL of TEOS, 0.5 g of Triton X-100 and 50 mL of deionized water were injected into the nanomagnetic beads in sequence. After ultrasonic treatment for 10 min, a brown emulsion was obtained. Under stirring, 50 mL of ethanol and 18 mL of 25% ammonia water were added. The mixture was reacted at room temperature for 4 h. The mixture was collected by magnetic extraction, washed with deionized water and dried in a vacuum oven at 40 °C. The black precipitate obtained was the silicon-coated modified Fe 3 O 4Nanomagnetic beads.

[0070] 4) Synthesis of magnetic particles grafted with polymer fibers:

[0071] According to the mass fraction, take 50 parts of distilled water, add 10 parts of polyvinyl alcohol (molecular weight>50000), after sufficient swelling, heat to 80℃ until the polyvinyl alcohol is completely dissolved, then add 50 parts of distilled water, and then add 2 parts of silicon-coated modified Fe 3 O 4 Nano magnetic beads, then add citric acid to adjust the pH to 4-6, stir and react for 30 minutes, then add 4 parts of butyraldehyde, react for 30 minutes, dehydrate and wash to obtain magnetic particles grafted with polyvinyl butyral fibers, that is, modified nano magnetic particles.

[0072] 5) Synthesis of magnetic particle grafted polymer fiber membrane fabric:

[0073] The modified nanomagnetic particles were dissolved in an ethanol solution, quickly and thoroughly stirred to obtain a spinning solution with a concentration of 10wt%, and then electrospinning was used to prepare magnetic particle grafted polyvinyl butyral fiber membrane fabric, wherein the electrospinning voltage was 12kV, the distance between the syringe needle and the receiving plate was 10cm, the flow rate of the spinning solution was 1mL / h, and the electrospinning time was 10min.

[0074] Figure 1 A schematic diagram of the synthesis of modified nanomagnetic particles prepared in Example 1 is shown.

[0075] Figure 2 The silicon-coated modified Fe prepared in Example 1 is shown 3 O 4 TEM image of nanomagnetic beads. It can be seen from the figure that the silicon-coated modified Fe 3 O 4 The particle size of the nanomagnetic beads is about 200 nm.

[0076] Example 2

[0077] 1)Fe 3 O 4 Synthesis of nanomagnetic beads:

[0078] In a 500mL three-necked flask, add 300mL of distilled water and pass N 2 Continue for 30 min, keep nitrogen atmosphere in the subsequent steps, add 5 g FeCl 3 6H 2 O, stir until all dissolved, then add 2g FeCl 2 ·4H 2 O, continue stirring until all dissolved, then heat to 80°C, add 20mL 25% ammonia solution, keep at 80°C for 4h to obtain Fe3 O 4 Nanomagnetic beads.

[0079] 2) Modified Fe 3 O 4 Synthesis of nanomagnetic beads:

[0080] Maintaining 80°C, add 250 mg of oleic acid (300 μL) in 5 mL of acetone, then add 5 mL of 28% ammonia water, continue stirring at 80°C for 30 min, then slowly cool to room temperature, separate the magnetic beads with a magnet, wash the separated magnetic beads with ethanol, and dry them to obtain modified Fe 3 O 4 Nanomagnetic beads.

[0081] 3) Silicon-coated modified Fe 3 O 4 Synthesis of nanomagnetic beads:

[0082] To modify Fe 3 O 4 Nanomagnetic beads were injected with 25 mL TEOS, 0.5 g Triton X-100 and 50 mL deionized water in sequence, and a brown emulsion was obtained after ultrasonic treatment for 10 min. Under mechanical vigorous stirring, 50 mL ethanol and 18 mL 25% ammonia water were added, and the reaction was carried out at room temperature for 4 h. The nanomagnetic beads were collected by magnetic extraction, washed with deionized water, and dried in a vacuum oven at 40 °C. The obtained black precipitate was the silicon-coated modified Fe 3 O 4 Nanomagnetic beads.

[0083] 4) Synthesis of magnetic particles grafted with polymer fibers:

[0084] According to the mass fraction, 50 parts of distilled water were added with 10 parts of polyhydroxy polyester fiber (molecular weight>50000). After sufficient swelling, the temperature was raised to 80°C until the polyhydroxy polyester fiber was completely dissolved. Then 50 parts of distilled water were added, and then 2 parts of silicon-coated modified Fe 3 O 4 Nano magnetic beads, then add citric acid to adjust the pH to 5.5-6.5, stir and react for 30 minutes, then add 4 parts of butyraldehyde, react for 30 minutes, dehydrate and wash to obtain magnetic particles grafted with polyester butyral fibers, that is, modified nano magnetic particles.

[0085] 5) Synthesis of magnetic particle grafted polymer fiber membrane fabric:

[0086] The modified nanomagnetic particles were dissolved in an ethanol solution, quickly and thoroughly stirred to obtain a spinning solution with a concentration of 10wt%, and then electrospinning was used to prepare magnetic particle-grafted polyester butyral fiber membrane fabric, wherein the electrospinning voltage was 12kV, the distance between the syringe needle and the receiving plate was 10cm, the flow rate of the spinning solution was 1mL / h, and the electrospinning time was 10min.

[0087] Comparative Example 1

[0088] 1) Silicon-coated Fe 3 O 4 Synthesis of nanomagnetic beads:

[0089] Weigh 5g FeCl 3 6H 2 O and 2 g FeCl 2 ·4H 2 O, dissolved in 60mL 0.1M HCl solution, dripped into 100mL 2M NaOH solution at 80℃ at a rate of 1 drop / s, then added 10mL 25% ammonia solution, stirred magnetically for 30min, cooled to room temperature, collected by magnetic extraction, washed with deionized water, then added to a 1000mL three-necked flask with 400mL ethanol and 10mL 25% ammonia solution, added 9mL TEOS in batches with a syringe, stirred continuously, then added 80mL distilled water, and reacted overnight. Collected by magnetic extraction, washed with deionized water, and dried in a vacuum oven at 40℃, the black precipitate obtained is the silicon-coated Fe 3 O 4 Nanomagnetic beads.

[0090] 2) Synthesis of magnetic particles grafted with polymer fibers:

[0091] According to the mass fraction, take 50 parts of distilled water, add 10 parts of polyvinyl alcohol (molecular weight>50000), and after sufficient swelling, heat it to 80°C until the polyvinyl alcohol is completely dissolved. Then add 50 parts of distilled water, and then add 2 parts of silicon-coated Fe 3 O 4 Nano magnetic beads, then add citric acid to adjust the pH to 4-6, stir and react for 30 minutes, then add 4 parts of butyraldehyde, react for 30 minutes, dehydrate and wash to obtain magnetic particles grafted with polyvinyl butyral fibers, that is, modified nano magnetic particles.

[0092] 3) Synthesis of magnetic particle grafted polymer fiber membrane fabric:

[0093] The modified nanomagnetic particles were dissolved in an ethanol solution, quickly and thoroughly stirred to obtain a spinning solution with a concentration of 10wt%, and then electrospinning was used to prepare magnetic particle grafted polyvinyl butyral fiber membrane fabric, wherein the electrospinning voltage was 12kV, the distance between the syringe needle and the receiving plate was 10cm, the flow rate of the spinning solution was 1mL / h, and the electrospinning time was 10min.

[0094] Figure 3 The silicon-coated Fe prepared in Comparative Example 1 is shown 3 O 4 TEM image of nanomagnetic beads. It can be seen from the figure that the silicon-coated Fe 3 O 4 The particle size of nanomagnetic beads is 20-30nm.

[0095] Comparative Example 2

[0096] 1)Fe 3 O 4 Synthesis of nanomagnetic beads:

[0097] In a 500mL three-necked flask, add 300mL of distilled water and pass N 2 Continue for 30 min, keep nitrogen atmosphere in the subsequent steps, add 5 g FeCl 3 6H 2 O, stir until all dissolved, then add 2g FeCl 2 ·4H 2 O, continue stirring until all dissolved, then heat to 80°C, add 20mL 25% ammonia solution, keep at 80°C for 4h to obtain Fe 3 O 4 Nanomagnetic beads.

[0098] 2) Modified Fe 3 O 4 Synthesis of nanomagnetic beads:

[0099] Maintaining 80°C, add 250 mg of oleic acid (300 μL) in 5 mL of acetone, then add 5 mL of 28% ammonia water, continue stirring at 80°C for 30 min, then slowly cool to room temperature, separate the magnetic beads with a magnet, wash the separated magnetic beads with ethanol, and dry them to obtain modified Fe 3 O 4 Nanomagnetic beads.

[0100] 3) Silicon-coated modified Fe 3 O 4 Synthesis of nanomagnetic beads:

[0101] To modify Fe 3 O 4Nanomagnetic beads were injected with 25 mL TEOS, 0.5 g Triton X-100 and 50 mL deionized water in sequence, and a brown emulsion was obtained after ultrasonic treatment for 10 min. Under mechanical vigorous stirring, 50 mL ethanol and 18 mL 25% ammonia water were added, and the reaction was carried out at room temperature for 4 h. The nanomagnetic beads were collected by magnetic extraction, washed with deionized water, and dried in a vacuum oven at 40 °C. The obtained black precipitate was the silicon-coated modified Fe 3 O 4 Nanomagnetic beads.

[0102] Comparative Example 3

[0103] 1) Silicon-coated Fe 3 O 4 Synthesis of nanomagnetic beads:

[0104] Weigh 5g FeCl 3 6H 2 O and 2 g FeCl 2 ·4H 2 O, dissolved in 60mL 0.1M HCl solution, dripped into 100mL 2M NaOH solution at 80℃ at a rate of 1 drop / s, then added 10mL 25% ammonia solution, stirred magnetically for 30min, and cooled to room temperature. Collected by magnetic extraction and washed with deionized water. Then added to a 1000mL three-necked flask with 400mL ethanol and 10mL 25% ammonia solution, added 9mL TEOS in batches with a syringe, stirred continuously, then added 80mL distilled water, and reacted overnight. Collected by magnetic extraction, washed with deionized water, and dried in a vacuum oven at 40℃, the black precipitate obtained is the silicon-coated Fe 3 O 4 Nanomagnetic beads.

[0105] Comparative Example 4

[0106] 1)Fe 3 O 4 Synthesis of nanomagnetic beads:

[0107] In a 500mL three-necked flask, add 300mL of distilled water and pass N 2 Continue for 30 min, keep nitrogen atmosphere in the subsequent steps, add 5 g FeCl 3 6H 2 O, stir until all dissolved, then add 2g FeCl 2 ·4H 2 O, continue stirring until all dissolved, then heat to 80°C, add 20mL 25% ammonia solution, keep at 80°C for 4h to obtain Fe 3 O 4 Nanomagnetic beads.

[0108] 2) Modified Fe 3 O 4 Synthesis of nanomagnetic beads:

[0109] Maintaining 80°C, add 250 mg of oleic acid (300 μL) in 5 mL of acetone, then add 5 mL of 28% ammonia water, continue stirring at 80°C for 30 min, then slowly cool to room temperature, separate the magnetic beads with a magnet, wash the separated magnetic beads with ethanol, and dry them to obtain modified Fe 3 O 4 Nanomagnetic beads.

[0110] 3) Silicon-coated modified Fe 3 O 4 Synthesis of nanomagnetic beads:

[0111] To modify Fe 3 O 4 Nanomagnetic beads were injected with 25 mL TEOS, 0.5 g Triton X-100 and 50 mL deionized water in sequence, and a brown emulsion was obtained after ultrasonic treatment for 10 min. Under mechanical vigorous stirring, 50 mL ethanol and 18 mL 25% ammonia water were added, and the reaction was carried out at room temperature for 4 h. The nanomagnetic beads were collected by magnetic extraction, washed with deionized water, and dried in a vacuum oven at 40 °C. The obtained black precipitate was the silicon-coated modified Fe 3 O 4 Nanomagnetic beads.

[0112] 4) Synthesis of magnetic particles grafted with polymer fibers:

[0113] According to the mass fraction, take 50 parts of distilled water, add 10 parts of polyvinyl alcohol (molecular weight>50000), after sufficient swelling, heat to 80℃ until the polyvinyl alcohol is completely dissolved, then add 50 parts of distilled water, and then add 2 parts of silicon-coated modified Fe 3 O 4 Nano magnetic beads, then add citric acid to adjust the pH to 4-6, stir and react for 30 minutes, then add 2 parts of formaldehyde, react for 30 minutes, dehydrate and wash to obtain magnetic particles grafted with polyvinyl alcohol formal fibers, that is, modified nano magnetic particles.

[0114] 5) Synthesis of magnetic particle grafted polymer fiber membrane fabric:

[0115] The modified nanomagnetic particles were dissolved in an ethanol solution, quickly and thoroughly stirred to obtain a spinning solution with a concentration of 10wt%, and then electrospinning was used to prepare magnetic particle grafted polyvinyl formal fiber membrane fabric, wherein the electrospinning voltage was 12kV, the distance between the syringe needle and the receiving plate was 10cm, the flow rate of the spinning solution was 1mL / h, and the electrospinning time was 10min.

[0116] Test Example 1

[0117] 1. Preparation before testing:

[0118] The fiber membrane fabrics prepared in Example 1, Comparative Example 1 and Comparative Example 4 were set on a cylindrical magnetic rod equipped with a magnetic rod set, and then 200 μL of the sample solution to be tested with known concentration, lysis binding solution, cleaning solution 1, cleaning solution 2 and elution solution were respectively added to the corresponding positions of the well plate, and the extraction program was set for extraction. Among them, different fiber membrane fabrics were required to complete three extractions in parallel to test their stability between batches.

[0119] The silicon-coated modified Fe prepared in Comparative Example 2 3 O 4 Nanomagnetic beads and silicon-coated Fe prepared in Comparative Example 3 3 O 4 Nanomagnetic beads were loaded into the corresponding positions of the well plate, and then 200 μL of the same sample solution, lysis binding solution, cleaning solution 1, cleaning solution 2, and elution solution were added to the corresponding positions of the well plate, and the same extraction procedure was set for extraction. 3 O 4 The nanomagnetic beads were used to complete three extractions in parallel to test their stability between batches.

[0120] Preparation of Qubit test sample solution: Take a total of 2985 μL (199 μL / sample * 15 samples) of solvent and mix it evenly with 15 μL of dye, then take 199 μL and add 1 μL of DNA solution of known concentration.

[0121] 2. DNA recovery test

[0122] The DNA recovery rate test used a DNA solution of known concentration as the test sample. The Qubit instrument was used to measure the concentration of the recovered sample after extraction and the recovery rate was calculated. The results are shown in Table 1.

[0123] Test Example 2

[0124] 1. Preparation before testing:

[0125] The fiber membrane fabrics prepared in Example 1, Comparative Example 1 and Comparative Example 4 were set on a cylindrical magnetic rod equipped with a magnetic rod set, and then 200 μL of real animal sample solution and lysis binding solution, cleaning solution 1, cleaning solution 2 and elution solution were respectively added to the corresponding positions of the well plate, and the extraction program was set for extraction. Among them, different fiber membrane fabrics were required to complete three extractions in parallel to test their stability between batches.

[0126] The silicon-coated modified Fe prepared in Comparative Example 2 3 O 4 Nanomagnetic beads and silicon-coated Fe prepared in Comparative Example 3 3O 4 Nanomagnetic beads were loaded into the corresponding positions of the well plate, and then 200 μL of the same real animal sample solution and lysis binding solution, cleaning solution 1, cleaning solution 2, and elution solution were added to the corresponding positions of the well plate, and the same extraction procedure was set for extraction. 3 O 4 The nanomagnetic beads were used to complete three extractions in parallel to test their stability between batches.

[0127] 2. Concentration and purity test

[0128] 1) The concentration test was performed using a Qubit instrument. The test results are shown in Table 1.

[0129] 2) Purity test was performed using Nanodrop instrument. 2 μL of the extracted DNA solution was taken and placed on the test bench for testing. The test results are shown in Table 1. The purity results between 1.7 and 1.9 indicate that the extraction purity is good.

[0130] Table 1

[0131]

[0132] It can be seen from Table 1 that after the cylindrical magnetic rod is wrapped with fiber membrane fabric, the recovery rate and concentration of extracted DNA are improved to a certain extent; by comparing the data of Example 1, Comparative Example 1 and Comparative Example 4, it can be found that the fiber membrane fabric synthesized in Example 1 has higher extraction performance and batch-to-batch stability.

[0133] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not limitations on the implementation methods of the present invention. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is impossible to list all the implementation methods here. All obvious changes or modifications derived from the technical solution of the present invention are still within the protection scope of the present invention.

Claims

1. A modified nanomagnetic particle, characterized in that: The modified nano-magnetic particles are magnetic particles grafted with polymer fibers; The polymer fiber is selected from one or more of polyvinyl acetal fiber, polyvinyl acetal derivative fiber, polyvinyl alcohol copolymer derivative fiber, polyvinyl pyrrolidone fiber, polyvinyl pyrrolidone derivative fiber, polyhydroxy polyester acetal fiber, and polyhydroxy polyester acetal derivative fiber.

2. The modified nanomagnetic particle according to claim 1, characterized in that: The magnetic particles have a core-shell structure, including a magnetic material as a core and a silicon coating layer as an outer shell; the magnetic material is selected from modified Fe3O4 nano-magnetic beads.

3. The modified nanomagnetic particles according to claim 2, characterized in that: The modified Fe3O4 nano-magnetic beads are Fe3O4 nano-magnetic beads whose surfaces are modified by silane or oleic acid.

4. The modified nanomagnetic particles according to claim 2, characterized in that: The groups contained in the polymer fiber are grafted onto the surface of the silicon coating layer through covalent bonds; The groups include, but are not limited to, one or more of amino, carboxyl, hydroxyl, amide, and ester groups.

5. The method for preparing the modified nanomagnetic particles according to any one of claims 1 to 4, characterized in that: The preparation method is carried out under an inert atmosphere and comprises the following steps: Add water to the polymer, raise the temperature to 80-95° C. after sufficient swelling, then add magnetic particles, adjust the pH to 4-6.5, add the blocking agent after stirring, and continue the reaction for 20-40 minutes to obtain the modified nano magnetic particles.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the magnetic particles, polymer and sealing agent is 1-2:10:2-4; The polymer is selected from one or more of polyvinyl alcohol, polyvinyl pyrrolidone and polyhydroxy polyester, and has a molecular weight of 50,000-80,000.

7. Use of the modified nanomagnetic particles according to any one of claims 1 to 4 or the modified nanomagnetic particles prepared by the preparation method according to claim 5 or 6 in cell sorting, immunoassay, nucleic acid analysis, biochip preparation and microbial detection.

8. A free nucleic acid extraction kit, characterized in that: The modified nanomagnetic particles include those described in any one of claims 1 to 4.

9. A magnetic particle grafted polymer fiber membrane fabric, characterized in that: The modified nanomagnetic particles are prepared using the modified nanomagnetic particles described in any one of claims 1 to 4 as raw materials.

10. The method for preparing the magnetic particle grafted polymer fiber membrane fabric according to claim 9, characterized in that: The steps include: The modified nano-magnetic particles are dissolved in an organic solvent, stirred evenly to obtain a spinning solution, and then electrostatic spinning is used to prepare the solution.

11. Use of the magnetic particle grafted polymer fiber membrane fabric according to claim 9 or the magnetic particle grafted polymer fiber membrane fabric prepared by the preparation method according to claim 10 in automatic extraction of nucleic acid.

12. The use according to claim 11, characterized in that: The applications include: The magnetic particle grafted polymer fiber membrane fabric is wrapped on the outer surface of the magnetic rod sleeve, and then the nucleic acid is extracted, cleaned and purified.